2018
DOI: 10.1029/2018jg004408
|View full text |Cite
|
Sign up to set email alerts
|

Yields and Characterization of Dissolved Organic Matter From Different Aged Soils in Northern Alaska

Abstract: Soil organic matter (SOM) in northern high-latitude regions is a major component of the global carbon cycle. However, the yield of soil-dissolved organic matter (DOM) during soil-water interactions and its chemical characteristics and reactivities remain poorly understood. We report here elemental composition and isotopic signatures of bulk-SOM from northern Alaska, and yields of water-leachable soil-DOM, including dissolved organic carbon, dissolved organic nitrogen, and dissolved organic phosphorus, and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 107 publications
(178 reference statements)
5
15
1
Order By: Relevance
“…It is thus possible that the frozen peat used in our study releases only labile OC at 4 and 25°C and that the excess of DOC observed at 45°C corresponds to the recalcitrant OM of peat. It should be further noted that in our study, the substrate-normalized DOC yields of frozen peat (~5 mg g − 1 peat) were substantially higher than the values obtained for organic soil samples of Alaska (0.14-2.2 mg g − 1 of soil, Gao et al, 2018).…”
Section: Doc Release From Frozen Peat At Different Temperaturescontrasting
confidence: 88%
“…It is thus possible that the frozen peat used in our study releases only labile OC at 4 and 25°C and that the excess of DOC observed at 45°C corresponds to the recalcitrant OM of peat. It should be further noted that in our study, the substrate-normalized DOC yields of frozen peat (~5 mg g − 1 peat) were substantially higher than the values obtained for organic soil samples of Alaska (0.14-2.2 mg g − 1 of soil, Gao et al, 2018).…”
Section: Doc Release From Frozen Peat At Different Temperaturescontrasting
confidence: 88%
“…Mechanistic reasons for the extremely low bioavailability of DOC from studied peatlands remain unclear and require an in-depth analysis of the DOM molecular structure and stoichiometry as well as high-resolution microbial approaches. It is known that the DOM released from frozen soils contains high proportions of biologically labile proteinlike and photochemically reactive aromatic substances (Gao et al, 2018). Following the pioneering study of Ward et al (2017), we hypothesize that, similar to DOC from the organic (non-permafrost) layer, the concentration of highly labile, aliphatic-like DOC in surface waters of frozen peatlands is too low to sustain microbial populations, or that this aquatic DOC, remaining after the microbial processing of soil pore-water DOC, is of low lability for microbes capable of degrading aliphatic-like DOC and inhabiting the aerobic zone of permafrost surface waters.…”
Section: High Stability Of Dom To Biodegradation In Surface Waters Frmentioning
confidence: 99%
“…Mechanistic reasons for extremely low bioavailability of DOC from studied peatlands remain unclear and require in-depth analysis of DOM molecular structure and stoichiometry as well as high resolution microbial approaches. It is known that the DOM released from frozen soils contains high proportions of biologically labile protein-like and photochemically reactive aromatic substances (Gao et al, 2018). Following the pioneering study of Ward et al 2017 associated with an increase in SUVA by up to 7.4 %, which also implies an increase in the proportion of aromatic compounds (Hulatt et al, 2014).…”
Section: Another Important Point Revealed In Previous Work On Biodegrmentioning
confidence: 99%